Формирование структурно-фазовых состояний, дефектной субструктуры и свойств поверхности термомеханически упрочнённой низкоуглеродистой стали - Громов, В.Е.; Иванов, Ю.Ф.; Белов, Е.Г.; Костерев, В.Б.; Косинов, Д.А. (Успехи физики металлов, 2016)
Проведено термомеханическое упрочнение стали 09Г2С путём прокатки балочного профиля ДП155 и принудительного охлаждения водой в потоке стана 450 ОАО «ЕВРАЗ Объединённый Западно-Сибирский металлургический комбинат». Методами просвечивающей дифракционной электронной микроскопии проведены исследования структурно-фазовых состояний и дефектной субструктуры балки из стали 09Г2С, формирующейся в результате термомеханического упрочнения в потоке прокатного стана. Проанализированы процессы и механизмы, способствующие формированию наноразмерной фазы в условиях термомеханической обработки низкоуглеродистой стали. На основе использования количественных параметров структуры стали, выявленных методами металлографии и электронной дифракционной микроскопии, и оценочных соотношений физического материаловедения выполнен анализ физических механизмов, ответственных за повышение микротвёрдости поверхностного слоя при термомеханическом упрочнении, и выявлены количественные параметры, характеризующие структурно-фазовое состояние и дающие возможности оценить величину теоретического предела текучести стали. Получено качественное соответствие изменения экспериментально измеренной микротвердости и теоретически определенного предела текучести по сечению полки профиля. Установлено, что явление повышения прочности поверхностного слоя стали является многофакторным, морфологически многокомпонентным и определяется природой γ→α превращения. Основными механизмами, ответственными за высокий уровень прочности поверхностного слоя стали, являются субструктурный и деформационный, обусловленные формированием кристаллов мартенсита и бейнита. Проведено термомеханічне зміцнення криці 09Г2С шляхом прокатки балочного профілю ДП155 та примусового охолодження водою у потоці стану 450 ВАТ «ЄВРАЗ Об’єднаний Западно-Сибірський металургійний комбінат». Методами просвічувальної дифракційної електронної мікроскопії проведено дослідження структурно-фазових станів і дефектної субструктури балки із криці 09Г2С, що формується в результаті термомеханічного зміцнення в потоці прокатного стану. Проаналізовано процеси та механізми, що сприяють формуванню нанорозмірної фази в умовах термомеханічної обробки низьковуглецевої криці. На основі використання кількісних параметрів структури криці, що виявлено методами металографії й електронної дифракційної мікроскопії, та оцінювальних співвідношень фізичного матеріялознавства виконано аналізу фізичних механізмів, відповідальних за підвищення мікротвердости поверхневого шару при термомеханічному зміцненні, та виявлено кількісні параметри, що характеризують структурно-фазовий стан і дають можливості оцінити величину теоретичної межі плинности криці. Одержано якісна відповідність зміни експериментально міряної мікротвердости і теоретично визначеної межі плинности за перерізом полки профілю. Встановлено, що явище підвищення міцности поверхневого шару криці є багатофакторним, морфологічно багатокомпонентним і визначається природою γ→α перетворення. Основними механізмами, відповідними за високий рівень міцности поверхневого шару криці, є субструктурний і деформаційний, що обумовлені формуванням кристалів мартенситу та бейніту. Experimental investigations of structural and phase states being formed in a cross-section of products as a result of thermomechanical treatment are very significant for understanding the physical nature of transformations since they make it possible to change structure and mechanical characteristics purposefully. Thermomechanical hardening of low-carbon steel 09Г2C (0.09 wt.% of C, 2 wt.% of Mn, 1 wt.% of Si;) was made by rolling of H-beam ДП 155 and forced water cooling on rolling mill 450 of open joint-stock company ‘EVRAZ Consolidated West-Siberian Metallurgical Plant’. By methods of transmission diffraction electron microscopy, we investigated structural-phase states and defect substructure of H-beam (made of 09Г2С steel) formed during thermomechanical hardening on rolling mill. It is established that defect substructure state of steel αα-phase is determined by (a) the mechanisms of γ→α transformation, (b) the regime of high temperature rolling and accelerated cooling, (c) the distance to the surface of the accelerated cooling. The correspondence of dislocation substructure and morphology of αα-phase (mechanism of γ→α transformation) is established. In the martensite and bainite crystals, a net-like dislocation structure with a very high dislocation density that varies within the range of 5.8∙10¹⁰–10.0∙10¹⁰ cm⁻² is a dominant one. In the ferrite and pearlite grains, a structure of dislocation chaos and net-like dislocation substructure with a relatively low values of scalar density of dislocations varying within the range 2.6·10¹⁰–3.5·10¹⁰ cm⁻² are determined. We analyzed the processes and mechanisms contributing to the formation of nanodimensional phase at the thermomechanical treatment of low-alloy steel. It was shown as follows: (i) in dispersion of cementite plates of pearlite colonies by cutting them with moving dislocations, the particles of 5–30 nm size were formed; (ii) the oval-shape particles of 5–15 nm size were formed during the dissolution of cementite plates of pearlite colonies and repeated precipitation on dislocations, boundaries of subgrains and grains; (iii) during the decomposition of solid solution of carbon in the αα-iron occurring in the conditions of ‘self-tempering’ of martensite, the sizes of particles precipitated in the volume of martensite crystals on dislocations are 5–10 nm, and at the boundaries of martensite crystals—10–30 nm; (iv) during the diffusion γ→α transformation at the high degree of deformation and temperatures of treatment, a dispersion of lamellar pearlite structure is observed: thickness of αα-phase plates separated by the carbide plates is ≈ 70 nm, while thickness of carbide phase plates is ≈ 25 nm. Using the quantitative parameters of steel structure revealed by the methods of metallography and electron diffraction microscopy, and estimate relations of physical material science, we analyzed physical mechanisms responsible for enhancement the microhardness of surface layer at the thermomechanical hardening. The quantitative parameters characterizing structural and phase state and allowing the possibilities to estimate the value of theoretical yield point for steel were determined. The quantitative correspondence of change of experimentally measured microhardness and theoretically determined yield point along the cross-section of H-beam flange was obtained. It is established that the phenomenon of increase in hardness of steel surface layer is a multi-factor, morphologically multi-component one, and is determined by the nature of γ→α transformation. The main mechanisms responsible for high level of steel surface layer hardness are substructural and deformational ones caused by the formation of martensite and bainite crystals